Sistem Pakar Deteksi Kerusakan Laptop Menggunakan Algoritma Forward Chaining Dan Backward Chaining - Azis Fikri Marsandi; Adi Rizky Pratama; Dwi Sulistya Kusumaningrum; Tatang Rohana (STMIK Budi Darma, 2024)
An expert system is an information system that contains the thoughts and knowledge of an expert in solving specific problems. Therefore, expert systems are considered effective and beneficial solutions for diagnosing laptop malfunctions. This application is developed using PHP programming language with MySQL as the database. The data obtained from a field expert and relevant journals on laptop malfunctions is then entered into the database and processed to display analysis results and solutions. The development of this expert system can be used to identify laptop malfunction symptoms, making initial diagnosis easier and providing knowledge to the general public who may not understand the early symptoms of laptop malfunctions. In this study, a software application is designed to assist in diagnosing laptop malfunctions. This application is expected to help users diagnose laptop malfunctions using forward chaining and backward chaining algorithms. Based on expert testing, the confidence level obtained is 87% for the forward chaining algorithm and 81% for the backward chaining algorithm